2003
DOI: 10.1063/1.1563293
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the refractive indices of AlN, GaN, and AlxGa1−xN grown on (111)Si substrates

Abstract: The refractive indices of several AlxGa1−xN alloys deposited on silicon are determined by ellipsometry and reflectivity experiments at room temperature. The AlGaN layers are grown on (111)Si substrate by molecular-beam epitaxy on top of an AlN/GaN/AlN buffer in order to reduce the strain of the alloy. The Al composition is deduced from energy dispersive x-ray spectroscopy and photoluminescence experiments. The refractive index n and the extinction coefficient k are determined in the 300–600 nm range. For the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 25 publications
4
50
1
Order By: Relevance
“…5 Although the III-nitride based devices are key elements for the development of new highly efficient LEDs and lasers, their reliability and efficiency depends strongly on the precise knowledge of optical constants. 6 Thin films of GaN, AlN, and their alloys have been deposited by a variety of deposition processes including sputtering, 7,8 metal-organic chemical vapor deposition (MOCVD), [9][10][11] plasma enhanced-CVD, 12 molecular beam epitaxy (MBE), 13,14 and atomic layer deposition (ALD). [15][16][17] During the last decade, numerous papers have been published on the deposition of epitaxial layers of GaN, AlN, and their alloys using both the MOCVD and MBE methods.…”
Section: à4mentioning
confidence: 99%
“…5 Although the III-nitride based devices are key elements for the development of new highly efficient LEDs and lasers, their reliability and efficiency depends strongly on the precise knowledge of optical constants. 6 Thin films of GaN, AlN, and their alloys have been deposited by a variety of deposition processes including sputtering, 7,8 metal-organic chemical vapor deposition (MOCVD), [9][10][11] plasma enhanced-CVD, 12 molecular beam epitaxy (MBE), 13,14 and atomic layer deposition (ALD). [15][16][17] During the last decade, numerous papers have been published on the deposition of epitaxial layers of GaN, AlN, and their alloys using both the MOCVD and MBE methods.…”
Section: à4mentioning
confidence: 99%
“…The spectra of all samples also show a yet unidentified transition at photon energy of about 13 eV. Antoine-Vincent et al reported optical constants in the 300-600 nm range for several Al compositions of Al x Ga 1-x N alloy layers grown on (111) Si substrates [108]. An accurate knowledge of the refractive indices of AlGaN alloys will be helpful for effective design of devices.…”
Section: R D'costa Et Almentioning
confidence: 83%
“…Experimental transmission spectra were compared with theoretical calculations using a three layer model (substrate/buffer layer/InN) [14] to obtain values of thickness, ordinary refractive index n 0 (), and absorption coefficient () of the InN layer. A sigmoidal approximation was used for () [15], meanwhile n 0 () was obtained in the transparency region considering a first order Sellmeier dispersion formulas [16]. Scattering from rough surface is included in the calculations follow the model proposed by Filinski [17].…”
Section: Resultsmentioning
confidence: 99%